Pelatihan Pembuatan Media Pembelajaran Berbasis E-Learning bagi Pengajar di Lembaga Pendidikan Luar Sekolah - A'am Rifaldi Khunaifi; Arif Supriyadi; Bayu Suratmoko (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The rapid development of information and communication technology or what is known as Information and Communication Technology (ICT) has penetrated various fields of life, including education and teaching. With regard to learning, the use of information technology, in this case, e-learning, is needed not only for educators who are skilled at utilizing technology and technology for the manufacture of teaching materials, but a design is needed to carry out learning effectively. In a learning design (instructional design) there is a process to guide actors (actors) to design, develop, implement e-learning content by utilizing the available e-learning infrastructure and applications. At the next stage in the implementation of e-learning, there is an evaluation stage which is used to revise or adjust to the previous stages. A good educational institution must develop teachers by providing various facilities to support the teaching and learning process. Teachers can replace it with a new method in the form of video or audio that has been combined with the teaching material they want to convey. As technology develops, mobile or smartphone versions of e-Learning can be compatible with the features available in conventional learning so that the quality of content in the form of subject matter can be accessed properly.